EFEKTIVITAS BUDAYA ORGANISASI PELAYANAN PUBLIK (STUDI KASUS DI BEBERAPA RUMAH SAKIT PEMERINTAH DI KOTA MEDAN) - Jufrizen Radiman (Jurnal Riset Akuntansi dan Bisnis, 2010)
The purpose of this study are relevant to the formulation of the previousproblem, namely to assess and analyze the effectiveness of the organizational cultureof public service in government-owned hospitals in Medan. Sources of data in thisstudy originated from the primary data. Primary data collected by the researchersconducted through questionnaires, interviews and observation. Population in thisresearch is all employees of government-owned hospitals from various manageriallevels of non-structural parts of existing tenure of more than one year. Randomsampling is based on a simple grouping of work. Maisng determined sample size ofeach population of 30 people from each employee in non-structural Hospital. Testingconstruct validity of the instrument to use validity. The results showed that theculture of organizations in government-owned hospital in Medan has effectivelysupport employee success.